2013
DOI: 10.1111/aas.12078
|View full text |Cite
|
Sign up to set email alerts
|

Minimum effective volume of ropivacaine 7.5 mg/ml for an ultrasound‐guided infraclavicular brachial plexus block

Abstract: For surgery distal to the elbow, the MEV in 95% of patients for an ultrasound-guided LSIB with ropivacaine 7.5 mg/ml was estimated to be 31 ml (95% CI, 18-45 ml). Further studies should determine the factors that influence the volume of local anaesthetic required for a successful infraclavicular block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…The existence of fascial layers may explain why injections of lesser volumes are less consistently successful when single injection techniques are used. 15,17 According to our observations, the injection of a greater volume may overcome the restriction of spread caused by a fascial layer (because of incomplete compartmentalisation). When 30 ml of dye was injected, a nearly satisfactory spread was achieved despite the presence of a posterolateral fascial layer ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The existence of fascial layers may explain why injections of lesser volumes are less consistently successful when single injection techniques are used. 15,17 According to our observations, the injection of a greater volume may overcome the restriction of spread caused by a fascial layer (because of incomplete compartmentalisation). When 30 ml of dye was injected, a nearly satisfactory spread was achieved despite the presence of a posterolateral fascial layer ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Our success rate with 20 ml of dye delivered as a single injection is similar to that reported by Flohr-Madsen and colleagues. 15 One major drawback of single injection ICB is the large volume of LA needed. Rettig and colleagues 16 demonstrated reduced or paradoxical hemidiaphragmatic movement in 26% of patients who had received ropivacaine 0.75% (0.5 ml kg À1 ) for ICB.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Despite the onslaught of new publications, the optimal methodology remains ambiguous. Whereas the Dixon-Mood up-and-down method remains most prevalent, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] recent trials have advocated using a Biased Coin Design variant. [27][28][29][30][31] Alternately, 3 studies published in 2013 used Bayesian analysis and the Continual Reassessment Method.…”
mentioning
confidence: 99%
“…We had assumed that the CC approach would produce more paresthesia than the LS approach, but we found that both groups experienced similar incidence (60%), and it was significantly higher than what is reported for the LS approach (0%-32%). 13,14,18,22,23 The exact reason for the high incidence of paresthesia in our study is not clear but may be because our patients were not sedated, as in the other reports. 13,14,18,22,23 Nevertheless, and in agreement with previous reports, 14 the paresthesia was transient and self-limiting, and none of our patients reported persistent neurological symptoms or signs at the 24-hour or 1-week follow-up after surgery.…”
Section: Discussionmentioning
confidence: 60%
“…13,14,18,22,23 The exact reason for the high incidence of paresthesia in our study is not clear but may be because our patients were not sedated, as in the other reports. 13,14,18,22,23 Nevertheless, and in agreement with previous reports, 14 the paresthesia was transient and self-limiting, and none of our patients reported persistent neurological symptoms or signs at the 24-hour or 1-week follow-up after surgery. Future randomized studies should evaluate the effects of preprocedural sedation and/or analgesia on the incidence of paresthesia and patient satisfaction during peripheral nerve blocks.…”
Section: Discussionmentioning
confidence: 60%